KILAS BALIK OPTIMALISASI PENCEGAHAN BERKEMBANGNYA PAHAM RADIKALISME DI WILAYAH HUKUM KEPOLISIAN RESORT CIMAHI - Ruhanda Ruhanda (FISIP Universitas Langlangbuana, 2019)
The development of the understanding of radicalism in the community is a threat, so the handling must be done systematically, tactically and strategically, especially for Binmas units in their jurisdiction. The complexity of this problem certainly cannot be claimed that the development of radical understanding is optimal, because in this prevention effort it is not only the task of the police but is related to other agencies especially in establishing communication and coordination for early detection of potential vulnerabilities from radical understandings that could continue to spread slowly and affect the attitudes of community members who are in conflict with the norms and regulations. Personnel of the Cimahi Regional Police Binmas Unit have made efforts through community coaching and counseling but the approach model adopted has not been optimally implemented, because this approach is not only among religious leaders, community leaders and youth leaders in but with the limited personnel of the society has not been touched as a whole. In this research based on the data obtained by the part that really needs support in preventing the development of radicalism understanding, so that the anticipatory steps towards the development of radicalism understanding. in the area of ​​cimahi police precincts can be overcome, so that the role of the national police So that realistic support is needed to increase the role of the Cimahi Regional Police Binmas Unit